Improving the electrochemical oxidation of formic acid by tuning the electronic properties of Pd-based bimetallic nanoparticles - Hu, Shuozhen; Che, Fanglin; Khorasani, Bita; Jeon, Mina; Yoon, Chang Won; McEwen, Jean-Sabin; Scudiero, Louis; Ha, Su (ELSEVIER, 2019)
Pd-based bimetallic nanoparticles have superior electrochemical activity and stability for formic acid oxidation (FAO) than pure Pd. Previous DFT-based calculations show that the catalytic properties of the Pd surface could be altered by modifying its electronic properties. However, only a few experimental studies investigate how the electronic properties of Pd are modified by introducing various metals and how the resulting electronic perturbation affects its electrochemical activity and stability for FAO. Here, we demonstrate a correlation between electrochemistry and electronic properties for Pd-M bimetallic nanoparticles (M = Ru, Pt, Cu, Au, and Ag). The volcano shape relationship obtained between activity and d-band center values suggests that the electronic effects play a major role in modifying the surface electrochemical properties of Pd-M bimetallic nanoparticles for FAO. Among all the bimetallic catalysts investigated in this study, Pd-Pt/C and Pd-Cu/C with d-band center values of 2.58 eV and 2.85 eV, respectively, demonstrate the highest activities and Pd-Cu/C exhibits the highest stability for FAO.
Keywords: TOTAL-ENERGY CALCULATIONS; CORE-SHELL NANOPARTICLES; MOLECULAR-DYNAMICS; FACILE SYNTHESIS; CATALYSTS; SURFACE; DECOMPOSITION; PERFORMANCE; ALLOY; SIZE